2016
DOI: 10.3389/fpls.2016.01445
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Evolution Analysis of Trehalose-6-Phosphate Synthase Gene Family in Nelumbo nucifera

Abstract: Trehalose-6-phosphate synthase (TPS) plays a key role in plant carbohydrate metabolism and the perception of carbohydrate availability. In the present work, the publicly available Nelumbo nucifera (lotus) genome sequence database was analyzed which led to identification of nine lotus TPS genes (NnTPS). It was found that at least two introns are included in the coding sequences of NnTPS genes. When the motif compositions were analyzed we found that NnTPS generally shared the similar motifs, implying that they h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…TPS, known as the crucial catalytic enzyme in trehalose accumulation, plays a vital role in abiotic stress tolerance and plant development. The genome-wide identification and characterization of TPS family genes have been conducted in Arabidopsis [ 14 ], rice [ 15 ], poplar [ 13 ], potato [ 62 ], lotus [ 63 ], apple [ 64 ], cotton [ 65 ], and Moringa oleifera [ 44 ]. There have been no systematic studies focused on the biological functions of the TPS family in P. mume .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPS, known as the crucial catalytic enzyme in trehalose accumulation, plays a vital role in abiotic stress tolerance and plant development. The genome-wide identification and characterization of TPS family genes have been conducted in Arabidopsis [ 14 ], rice [ 15 ], poplar [ 13 ], potato [ 62 ], lotus [ 63 ], apple [ 64 ], cotton [ 65 ], and Moringa oleifera [ 44 ]. There have been no systematic studies focused on the biological functions of the TPS family in P. mume .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with studies in sunflower and soybean, which have reported that positive selection forces could drive the divergence of gene function in the same clades by accelerating the retention of favorable amino acid mutations [ 67 , 68 ]. Evolutionary analyses in soybean [ 68 ], potato [ 62 ], lotus [ 63 ], poplar, and salix [ 69 ] have revealed that amino acid substitutions can result in genetic functional divergence [ 53 , 70 ]. Therefore, the genetic functional divergence of the TPS family was analyzed by DIVERGE to identify the crucial amino acid substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was conducted using the LightCycler ® /LightCycler ® 96 System Real Time PCR (Roche, Basel, Switzerland) with SYBR Premix Ex Taq II (TaKaRa, Kusatsu, Japan). The actin gene (GeneBank: ) was used as an internal control for normalization of the expression levels of candidate NnbHLHs among different samples, following previous studies (Cheng et al, 2013; Diao et al, 2014; Jin et al, 2016), and expression levels were calculated using the delta–delta CT method (Livak & Schmittgen, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…TPS plays a key role in the perception of carbohydrate availability and carbohydrate metabolism (Jin et al, 2016 ) in insects, other invertebrates, as well as in plants (Gao et al, 2014 ). TPS is considered a cytoplasmic protein with two functionally distinct catalytic domains (Elbein et al, 2003 ; Matsuda et al, 2015 ).…”
Section: Physiological Functionmentioning
confidence: 99%